Pengolahan Sampah Rumah Tangga Yang Mudah Dan Murah Sebagai Pupuk Organik Untuk Pelestarian Lingkungan Melalui Metode Takakura: Household Waste Treatment that Easy and Inexpensive as Organic Fertilizer for Environmental Conservation Through the Takakura Method - Ni Wayan Sri Suliartini; Isnaini Isnaini; Lutfatul Khaifa; Uzunu Ihwanul Aini; Muhammad Rafly Firdaus; Sekar Sari Bintang Solehah; Gina Tasya Rizka Hafizah (Jurnal Gema Ngabdi, 2022)
Household waste is a type of waste that contributes to environmental pollution. The more household activities are carried out, the more waste is produced, so proper waste management is a must. Waste processing by the community is done conventionally, it takes a long time to decompose. The takamura method is an innovation in waste processing by reusing waste into compost. The aim of this activity is to process household organic waste into compost. This is done to help the community in dealing with the problem of organic waste in their environment into a new product. This activity was carried out from January 24 to February 10, 2022 in Ranjok Village, Gunung Sari District. West Lombok. The method used is lecture, discussion and demonstration. Socialization and presentations are expected to increase public knowledge about the importance of processing household organic waste into products that can be reused so as to reduce environmental pollution. The demonstration was carried out by involving the active participation of the community on techniques for processing organic waste into compost. This activity received a positive response from the community and village officials because it can help reduce the volume of waste generated. The results of Community Service activities are increasing public awareness in organic waste management and understanding techniques for processing organic waste into compost starting from preparing Takakura baskets, adding bacteria fermenting organic matter, to the decomposition process